2001
DOI: 10.1089/152581601750098372
|View full text |Cite
|
Sign up to set email alerts
|

Immortalized Multipotential Mesenchymal Cells and the Hematopoietic Microenvironment

Abstract: In an attempt to analyze the cellular and molecular basis of the capacity of bone marrow stromal cells to support hematopoiesis in culture, we developed a series of murine stromal cell lines from a single long-term bone marrow culture (BMC). The cytokines produced by these cells were analyzed using immunohistochemical techniques, ribonuclease protection assays (RPA) and RT-PCR. We examined the capacity of these cloned cell lines to replace primary bone marrow-derived stromal cells in long-term bone marrow cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
70
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 52 publications
10
70
0
Order By: Relevance
“…Related studies have indicated that functional recovery in rodent ischemic stroke models is associated with collateral sprouting of the uninjured CST to the denervated side of spinal cord and is enhanced by treatment of inosine , bFGF (Kawamata et al, 1997), Nogo antibody (Papadopoulos et al, 2002) and Nogo receptor antagonist (Lee et al, 2004). Based on our and other studies, the BMSCs transplanted into the ischemic brain environment may provide their beneficial effects by secretion of neurotrophins and growth factors, including BDNF (Dormady et al, 2001;Li et al, 2002) and VEGF (Chen et al, 2003a). BMSC treatment can also reduce the gliosis and scar formation in the ischemic brain (Li et al, 2005).…”
Section: Discussionmentioning
confidence: 57%
“…Related studies have indicated that functional recovery in rodent ischemic stroke models is associated with collateral sprouting of the uninjured CST to the denervated side of spinal cord and is enhanced by treatment of inosine , bFGF (Kawamata et al, 1997), Nogo antibody (Papadopoulos et al, 2002) and Nogo receptor antagonist (Lee et al, 2004). Based on our and other studies, the BMSCs transplanted into the ischemic brain environment may provide their beneficial effects by secretion of neurotrophins and growth factors, including BDNF (Dormady et al, 2001;Li et al, 2002) and VEGF (Chen et al, 2003a). BMSC treatment can also reduce the gliosis and scar formation in the ischemic brain (Li et al, 2005).…”
Section: Discussionmentioning
confidence: 57%
“…They are polypeptides noted for their neurotrophic activity in the peripheral and central nervous system and might also be implicated in hematopoietic cells. 33,34 IGF-1 is a mediator of the action of growth hormone on normal tissues and it performs multiple functions, including cell proliferation and inhibition of apoptosis in hematopoietic cells. 35 The similarity in the expression profiles of AGM cells and C17.2 is in line with recent proposals on the close relationship between hematopoiesis and neuropoiesis during embryonic development and in the manifestation of 'adult stem cell plasticity'.…”
Section: Discussionmentioning
confidence: 99%
“…7 MSCs contain a population of cells that are self-renewing, and are capable of differentiating into multiple mesodermal tissues, including bone, cartilage, fat and muscle. 8 They produce many neurotrophic factors and cytokines, 9 can assume other phenotypes, suppress inflammation and trigger production of reparative growth factors as demonstrated after transplantation into other organ systems such as the lung 10 and heart. 11 Potential advantages of MSCs over other types of transplanted cells are shown in Table 1 which include their ability to be harvested from autologous donors, their relatively rapid expansion ex vivo and the possibility that allogeneic MSCs are nonimmunogenic and, hence, readily available for clinical use, 12 although some studies have indicated that immune suppression improves transplant survival.…”
Section: Introductionmentioning
confidence: 99%